The Prevalence of Posttraumatic Stress Disorder Among Survivors After a Typhoon or Hurricane: A Systematic Review and Meta-Analysis. (December 2019) - Wang, Zhipeng; Wu, Xin; Dai, Wenjie; Kaminga, Atipatsa C.; Wu, Xiaoli; Pan, Xiongfeng; Liu, Ziyan; Wen, Shiwu; Hu, Shixiong; Liu, Aizhong
ABSTRACT: Posttraumatic stress disorder (PTSD) is a psychological disorder, which could be caused by traumatic events. The prevalence of PTSD among survivors after a typhoon or hurricane varied widely. Therefore, this study aimed to determine a combined prevalence of PTSD among survivors after a typhoon or hurricane. A systematic search of literature was performed in the 3 English databases: PubMed (National Library of Medicine, Bethesda, MD), ISI Web of Science (Thomson Reuters, New York, NY), and Embase (Elsevier, Amsterdam, Netherlands). Also, a similar search was performed in the 2 Chinese databases such as Chinese National Knowledge Infrastructure and WanFang. Loney et al.'s criteria were used to evaluate the quality of the selected articles for this study. The combined prevalence of PTSD among the study population was estimated using the Freeman–Tukey double arcsine transformation method. Subgroup analyses and a meta-regression analysis were carried out to explore the origin of heterogeneity. Thirty-nine eligible articles were included in this study. They comprised 43 123 typhoon and hurricane survivors of which 9373 were diagnosed with PTSD. The combined prevalence of PTSD among this population was 17.81%. Subgroup analyses revealed that the combined prevalence of PTSD related to typhoon and hurricane Categories 5, 4, and 2 showing a corresponding decreasing tendency. About 18% of people who experienced a severe typhoon or hurricane develop PTSD with the prevalence decreasing with reduced severity of the typhoon or hurricane.